Zinc Oxide Based Nanomaterials and Their Application in the Removal of Toxic Contaminants for Waste Water - Matilda, Manasseh Ilumunter; Umaru, Isaac John; Umaru, Kerenhappuch Isaac; Akram, Muhammad (Darul Yasin Al Sys, 2025)
The increasing global demand for clean water underscores the urgency of addressing environmental pollution, particularly through effective wastewater treatment. Rapid urbanization, population growth, and industrial expansion have significantly contributed to the degradation of water quality, making contamination a persistent and complex challenge. Despite numerous scientific efforts to develop remediation strategies, many existing techniques remain difficult to replicate or scale down effectively for widespread application. In this context, nanotechnology has emerged as a promising field, offering innovative solutions for environmental remediation. Among various nanomaterials, zinc oxide (ZnO) nanoparticles stand out due to their unique physicochemical and optical properties, which are substantially enhanced at the nanoscale. ZnO nanoparticles have gained considerable attention in material science, especially for their applications in photocatalysis, antimicrobial treatments, and environmental detoxification. However, their synthesis and functional performance are highly sensitive to several factors, including the pH of the reaction medium, calcination temperature, reaction time, stirring speed, the nature of capping agents, and the concentration of metal precursors. These variables critically influence the size, morphology, and surface activity of ZnO nanoparticles, thereby determining their effectiveness in water treatment applications. Understanding and optimizing these synthesis parameters are crucial for enhancing the reproducibility, efficiency, and scalability of ZnO-based nanotechnologies in real-world environmental contexts.